Retrato linguístico da fala do interior paulista: 20 anos do Projeto ALIP (Amostra Linguística do Interior Paulista) - Rubio, Cássio Florêncio [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
This report presents the results of a postdoctoral internship whose objective is to organize a compendium describing the characteristics, peculiarities, and linguistic phenomena present in the linguistic variety of the São José do Rio Preto region, encompassing linguistic phenomena at the phonetic-phonological, morphosyntactic, and textual-discursive levels. The corpus includes the research already conducted over the nearly two decades of existence and availability of the ALIP Project's linguistic samples. The study, of a bibliographic nature, was conducted through a thorough review of the research already conducted throughout the history of the ALIP Project, considering, firstly, the level of analysis in which they were included. This allowed for the description of the linguistic patterns of each level, whether variable or categorical, aiming to compose a (socio)linguistic portrait of the region's speech, highlighting features common to other varieties and characteristics that are only present in the region's variety. This collection of data and information allows for the production of unique, systematized, and functional material that provides a more complete understanding of the speech of the Northwest region of São Paulo State and supports comparative studies with other varieties. It also supports teaching proposals that connect with the language in use, particularly in the region covered by the ALIP Project. The development of this research was linked to the activities of the Sociofunctionalist Studies Group (GESF), an interinstitutional and international group that brings together researchers from Brazilian and international universities, whose studies are conducted using language samples in real-life situations. Thus, the proposal enabled the author to establish new academic and scientific partnerships.
A Linguistic portrait of the speech of São Paulo: 20 years of the ALIP Project (Linguistic Sample of the Interior of São Paulo)
foram identificadas mais de 100 produções acadêmicas relacionadas ao Banco de Dados Iboruna, as quais foram catalogadas e analisadas, com o objetivo de eliminar sobreposições, repetições de conteúdo, chegando-se ao total de 64 trabalhos sobre objetos de pesquisa distintos. Esse levantamento contemplou produções vinculadas a múltiplas instituições (UNESP, UFSCar, UFMS, USP, dentre outras) e diferentes linhas e correntes teóricas (sociolinguística, funcionalismo, gramática discursivo-funcional, gramaticalização, análise do discurso etc.). As obras foram organizadas em planilhas, categorizadas segundo o nível de análise linguística (fonológico, morfossintático, semântico-pragmático,textual-discursivo), escopo temático e abordagem teórica adotada.
Keywords: Descrição linguística; Português brasileiro; Banco de dados Iboruna